Prevalence, characteristics and outcome of non-cardiac chest pain and elevated copeptin levels. Issue 21 (26th June 2014) - Stallone, Fabio; Twerenbold, Raphael; Wildi, Karin; Reichlin, Tobias; Rubini Gimenez, Maria; Haaf, Philip; Fuechslin, Nicole; Hillinger, Petra; Jaeger, Cedric; Kreutzinger, Philipp; Puelacher, Christian; Radosavac, Milos; et al.
Abstract : Objective: Copeptin, a quantitative marker of endogenous stress, seems to provide incremental value in addition to cardiac troponin in the early rule-out of acute myocardial infarction (AMI). Prevalence, characteristics and outcome of acute chest pain patients with causes other than AMI and elevated copeptin are poorly understood. Methods: A total of 984 consecutive patients with non-cardiac chest pain were selected from a prospective multicentre study of acute chest pain patients presenting to the emergency department. Levels of copeptin were determined in a blinded fashion and considered elevated if above 13 pmol/L (the 97, 5th centile of healthy individuals). The final diagnosis was adjudicated by two independent cardiologists. Median duration of follow-up was 756 days. Results: Elevated copeptin levels were seen in 215 patients (22%). In comparison to patients with normal copeptin levels, patients with elevated levels were older, had more pre-existing cardiac and non-cardiac disorders, more silent cardiomyocyte injury and increased haemodynamic stress as quantified by levels of high-sensitivity cardiac troponin T (9.6 ng/L (3.6–18.3) vs 5.8 ng/L (2.9–9.4)) and B-type natriuretic peptide (75 ng/L (37–187) vs 35 ng/L (15–77)) (both p<0.001), more electrocardiographic abnormalities, more often an adjudicated diagnosis of gastroesophageal reflux or bronchitis/pneumonia and higher 2- year mortality (HR 2.9, 95% CI 1.5  to 5.7). The increased mortality rate seemed to be largely explained by age and comorbidities. Conclusions: Elevated levels of copeptin are present in about one in five patients with non-cardiac chest pain and are associated with aging, cardiac and non-cardiac comorbidities as well as mortality.